2014
DOI: 10.1097/bor.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and mucosal inflammation as extra-articular triggers for rheumatoid arthritis and autoimmunity

Abstract: Purpose of Review Despite progress towards understanding the molecular pathogenesis of Rheumatoid Arthritis (RA), its etiology remains elusive. Genes are important but rather insufficient to explain the majority of RA cases. This review describes novel data supporting the microbiome and its interactions with the human host as potential en(‘in’)vironmental factors in RA pathogenesis. Recent Findings Animal models of inflammatory arthritis have shown that the presence of bacteria in mucosal surfaces is suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
169
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 59 publications
(49 reference statements)
0
169
0
6
Order By: Relevance
“…In striking contrast, no overall effect was seen for respiratory infections: sinusitis, tonsillitis or pneumonia. This could be particularly interesting in light of emerging data implicating that the microbiome in the gut may play a role in RA pathogenesis since mucosal sites are exposed to a high load of bacterial antigens and may thus represent the site of initiation or modification of inflammation in RA 2 3 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In striking contrast, no overall effect was seen for respiratory infections: sinusitis, tonsillitis or pneumonia. This could be particularly interesting in light of emerging data implicating that the microbiome in the gut may play a role in RA pathogenesis since mucosal sites are exposed to a high load of bacterial antigens and may thus represent the site of initiation or modification of inflammation in RA 2 3 10…”
Section: Discussionmentioning
confidence: 99%
“…A second, and partly related, potential explanation would be that infections in the gut and urinary tract may change the composition of the microbiome and that such a change would influence the susceptibility to RA. Hypotheses on connections between inflammation and microbial composition in the gut and risk for RA have been raised and discussed for many years13 14 and recently reports from basic science suggest that changes in the gut microbiome may play a role in the pathogenesis of RA 2 3 10. In this context, we note with interest that the sites of infections that conferred a decreased risk in this study are primarily infected with gram-negative bacteria, while the sites in which infections did not confer a decreased risk are primarily infected with gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that, by virtue of their constant exposure to bacterial antigens, the lungs may be a potential site of early events that facilitate the initiation and, or progression of RA. While there have not been any studies that directly examined the role of the lungs and their microbiota in patients with RA, several studies suggest that the lungs may be susceptible to proinflammatory microbiota originating from periodontal tissue 123. First off, the respiratory mucosa houses their own unique set of microbiota that can be come perturbed in disease states 124 125.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The local effects of the PAMPs can also include increased corrosion of titanium surfaces, which in turn can increase PAMP binding to the surface [6]. Alternatively, gut-derived PAMPs could induce chronic low-level inflammation systemically [14,18,25,28,42,52,63,70,71,84,101,115], as appears to occur in the synovium during rheumatoid arthritis [12,106]. In this regard, it has recently been proposed that systemic low-level inflammation may contribute to aseptic loosening [81].…”
Section: Toll-like Receptorsmentioning
confidence: 99%